The Analysis of Interrelation between Kinetics of Propagation of Plastic Deformation and Initiation of Ductile Fracture - Laukhin, D.V.; Beketov, O.V.; Rott, N.O.; Tyuterev, I.A.; Ivantsov, S.V.; Laukhin, V.D. (Металлофизика и новейшие технологии, 2017)
The work analyses a nature of interrelation between kinetics of propagation of plastic deformation and initiation of ductile fracture for low-carbon microalloyed steel 06Kh1. To reach the purpose of the work, the experiment is carried out. It includes stretching of a series of samples with deformation deceleration after reaching a certain level of loading. The study of the corresponding samples shows that the stage of crack origination is made through blocking the propagation of spreading the plastic deformation by the separation surfaces of the general and special types. At the same time, it is determined that the second stage (growth of microcracks) develops due to the simultaneous action of two mechanisms: accumulation of dislocations (the Cottrell model) and aggregation of several microcracks into single one. В работе проанализирован характер взаимосвязи между кинетикой распространения пластической деформации и зарождением вязкого разрушения для низкоуглеродистой микролегированной стали 06Х1. Для достижения поставленной в работе цели был осуществлён эксперимент, который включал растяжение серии образцов с торможением деформации при достижении определённого уровня нагрузки. Исследование соответствующих образцов показали, что на стадии зарождения трещины её рост осуществляется путём блокирования распространения пластической деформации поверхностями раздела как общего, так и специального типа. Вместе с этим установлено, что вторая стадия (рост микротрещин) происходит за счёт одновременного действия двух механизмов: дислокационного накопления (модель Коттрелла) и объединения нескольких микротрещин в одну. У роботі проаналізовано характер взаємозв’язку між кінетикою поширення пластичної деформації та зародженням в’язкого руйнування для низьковуглецевої мікролеґованої сталі 06Х1. Для досягнення поставленої в роботі мети було здійснено експеримент, який включав розтягання серії зразків з гальмуванням деформації по досягненні певного рівня навантаження. Дослідження відповідних зразків показали, що на стадії зародження тріщини її зростання здійснюється шляхом блокування поширення пластичної деформації поверхнями поділу як загального, так і спеціяльного типу. Разом з цим встановлено, що друга стадія (зростання мікротріщин) відбувається за рахунок одночасної дії двох механізмів: дислокаційного накопичення (модель Коттрелла) й об’єднання кількох мікротріщин в одну.